Teknik Radioterapi Kanker Payudara Post Mastektomi dengan Teknik Intensity Modulated Radiation Therapy - Nursama Heru Apriantoro; Yudha Kartika (Universitas Muhammadiyah Ponorogo, 2023)
Breast cancer is one of the most common types of cancer in Indonesia, and is a malignancy in breast tissue that can originate from the ductal epithelium and its lobules. In cases after surgery (post mastectomy) it is necessary to carry out radiotherapy irradiation to clear the remnants of tumor cells on the chest wall and in the local lymph nodes, namely the axillary, supraclavicular, and some argue the internal mammary chain. The purpose of this study was to provide a description of the curative procedure and radiation dose for radiotherapy performed post mastectomy using the IMRT (Intensity Modulated Radiation Therapy) technique. The research method is descriptive qualitative with a participatory observation approach in post-mastectomy breast cancer patients. The modalities used are LINAC and CT Simulator, as a fixation tool a thermoplastic breast mask is used, with the patient in a supine position. The procedure was carried out in accordance with irradiation standards in general, in the irradiation plan a total external radiation dose of 5000 cGy and a fractional dose of 200 cGy were carried out for a total of 25 times of irradiation. In the fifth irradiation or multiples of the patient being controlled for Hb, the Hb level is 10, so the irradiation must be temporarily stopped until the Hb returns to normal.